Hak dan Kewajiban Suami–Istri dalam Fikih Klasik dan Kontemporer - Sugiri; Dayan Fithoroini; Yogie Fahrisal (Justicia Religia, 2025)
This study examines the formulation and evolution of spousal rights and obligations in classical and contemporary Islamic jurisprudence through a library research approach. Classical texts such as al-Majmu‘, al-Mughni, and Bidayat al-Mujtahid outline a normative structure of marital relations based on reciprocal duties, with economic maintenance (nafkah), mahr, and protection identified as primary obligations of the husband, while domestic management and obedience within lawful limits are traditionally assigned to the wife. Contemporary scholarship, however, demonstrates increasing reinterpretations driven by socioeconomic change, gender dynamics, and legal developments in Muslim-majority contexts, including Indonesia. Modern studies emphasize the necessity of contextualizing classical provisions to ensure alignment with maqāṣid al-syarī‘ah, particularly the principles of justice, dignity, and harm prevention (dar’ al-mafasid). The findings highlight that harmonizing classical jurisprudence with contemporary legal frameworks such as statutory reform and judicial practice offers a pathway toward a more equitable and responsive model of marital rights and responsibilities.